Why should I believe this? Deciphering the qualities of a credible online customer review. Issue 8 (17th November 2018) - Clare, Carl J.; Wright, Gillian; Sandiford, Peter; Caceres, Alberto Paucar
Abstract: Online customer reviews have been shown to have a powerful impact on the sales of a given product or service. However, the qualities of a 'credible' online customer review are still subject to debate. Existing research has highlighted the potential influence of a range of factors on the credibility of an online customer review, but relies heavily on quantitative methods and a 'top down' approach. In turn, this can reduce our understanding of the influence of these factors into merely discerning whether one pre-determined factor is more influential than another is. This paper adopted a 'bottom up' thematic analysis of individual qualitative interviews with a purposeful sample of consumers who regularly utilised online customer reviews. The findings uncovered a range of factors that influenced the credibility of an online customer review that were attached to a reader's personal experience and to the content of a specific review, and inferred the existence of a reciprocal relationship between the constructs of review helpfulness and review credibility.